Epoxy acrylate-based shape memory polymer via 3D printing - W. Shan; H. Zhong; H. Mo; S. Zhao; P. Liu (eXPRESS Polymer Letters, 2021)
Epoxy acrylate (EA) resin, due to its thermo-mechanical properties, performs excellent shaper memory properties. 3D printing opens new opportunities to fabricated shape memory polymer (SMP), which contributed to a rising variety of applications, also requires 3D-printable capability with more advanced shape-memory function and mechanical performance of the material. In this paper, a new strategy was developed to fabricate high strain EA-based SMP through digital light processing (DLP) 3D printing, which took advantage of free radical copolymerization of epoxy acrylate-based oligomer and monomers. The 3D-printed SMP showed high strain at break (up to 90%), thermal stability, as well as excellent shape memory performance. In addition, the shape memory-based self-driven electronics was fabricated by combining shape memory polymer with light-absorbing and conductive ink. The device could change its configuration in response to light and temperature, which has great potential application for soft robotics, flexible electronics, and intelligent control devices.